Signal Improvement for Underwater Measurement of Metal Samples Using Collinear Long-Short Double-Pulse Laser Induced Breakdown Spectroscopy - Cui, Minchao; Deguchi, Yoshihiro; Wang, Zhenzhen; Yao, Changfeng; Tan, Liang; Zhang, Dinghua (Frontiers in Physics, 2020)
A collinear long-short double-pulse laser induced breakdown spectroscopy (LS-DP-LIBS) is employed to detect the underwater metal samples. The emission spectra, time-resolved signal, plasma images and sound characteristics of plasma shockwave are experimentally investigated in this work. The results show that the underwater signal of Al, Cu and Fe spectral lines are significantly improved by collinear LS-DP-LIBS with inter-pulse delay of 35 us. The mechanism of the signal improvement is considered to be the pre irradiation effect of long pulse laser beam. In the collinear LS-DP-LIBS method, the long pulse firstly generates a cavitation bubble in water and provides the gaseous environment. Then the short pulse generates the plasma from sample surface. The present experiments show that the collinear LS-DP-LIBS method has acquired significantly signal improvement in underwater measurement of metal samples. This new method has great potential in deep-sea exploration using LIBS.